The Professor Emeritus Sa-nga Nilvarangkun, MD, Endowed Lectureship: National Policy & Sustainability on Thailand Dialysis Program - Supaporn, Thanom (Journal of the Nephrology Society of Thailand, 2024)
Short Biography Current Selected Positions: Senior Consultant in Nephrology and Internal Medicine, PhraMongkutklao Hospital. Senior Consultant in Nephrology and Internal Medicine, Office of Medical Services of The Permanent Secretary, Ministry of Defence Bangkok Thailand Advisor: Executive Committee of the Thai Society of Transplantation Past Selected Careers: Member of the Executive Committee of the Nephrology Society of Thailand (2001-2008) Chair: Thailand Renal Replacement Therapy subcommittee of the Nephrology Society of Thailand (2003-2008) Member of the National Health Security Office working committee to develop national renal replacement therapy policy recommendation in 2007 President of the Thai Transplantation Society (2017-2019)